Impact of Immunity in Autism Spectrum Disorders. (January 2013) - Tetè, S.; Varvara, G.; Murmura, G.; Saggini, A.; Maccauro, G.; Rosati, M.; Cianchetti, E.; Tripodi, D.; Toniato, E.; Fulcheri, M.; Caraffa, A.; Antinolfi, P.; et al.
Autism spectrum disorders (ASDs) are childhood psychopathologies characterized by having difficulties in social interaction, verbal and non-verbal communication as well as sensor motor movements. Evidence suggests that in ASDs environmental toxicant exposure, genetic and mitochondrial dysfunction are involved associated with abnormal immune response with allergic problems and elevated serum IgE. ASDs present the major cytokine and chemokine dysfunction in CNS and is mediated by an increase of pro-inflammatory cytokine levels in the brain, such as TNF, IL-1, IFN-γ, IL-6, IL-8 and others. Mast cells, which are also implicated in ASDs, are worsened by stress and produce proinflammatory cytokines and can be stimulated by neurotensin in the brain and gut, contributing also to the inflammatory response. However, the exact etiology of ASDs remains largely unknown.